Applications of viruses for cancer therapy - Tew, Kenneth D.; Fisher, Paul B.; Curiel, David (Advances in cancer research ;, 2012)
Provides information on the field of cancer research. It covers topics such as: Cancer Terminator Viruses and Approaches for Enhancing Therapeutic Outcomes, essign of improved oncolytic adenoviruses, and Adenovirus-based immunotherapies for cancer.